Traumatic Experiences and PTSD Among Adolescent Congolese Refugees in Uganda: A Preliminary Study - Ssenyonga, Joseph; Owens, Vicki; Kani Olema, David (Journal of Psychology in Africa, 2012)
The study examined experienced traumatic events and the related Post-Traumatic Stress Disorder (PTSD) amongst a sample of 89 adolescent Congolese refugees (56 females and 33 males) at a refugee camp in Uganda. Data was collected using a questionnaire, and analyzed for trauma moderation by demographics and mediation by PTSD symptom scores. Findings indicate a prevalence of PTSD of 49.4% overall, with 75% of the female refugees meeting the PTSD criteria. The refugees with PTSD had high intrusive, avoidance and arousal scores, in addition to moderate to severe PTSD symptom severity scores. Trauma load was a significant predictor of PTSD among adolescent refugees. Our findings point to the high prevalence of PTSD resulting from an increased trauma load and being a female.
Keywords: Traumatic experience; PTSD; Refugee; Refugee settlement camp